2012
DOI: 10.1093/bioinformatics/bts407
|View full text |Cite
|
Sign up to set email alerts
|

Event extraction across multiple levels of biological organization

Abstract: Motivation: Event extraction using expressive structured representations has been a significant focus of recent efforts in biomedical information extraction. However, event extraction resources and methods have so far focused almost exclusively on molecular-level entities and processes, limiting their applicability.Results: We extend the event extraction approach to biomedical information extraction to encompass all levels of biological organization from the molecular to the whole organism. We present the onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 32 publications
0
126
0
Order By: Relevance
“…mTOR consists of abstracts referenced as evidence for reactions curated in the mTOR signalling pathway [25], annotated for entities and events relevant to the pathway model formalism [7]. Multi-Level Event Extraction (MLEE) consists of abstracts in the blood vessel development subdomain that have been annotated using a comprehensive set of entity and event types encompassing levels of biological organisation from molecule to organism [26]. …”
Section: Methodsmentioning
confidence: 99%
“…mTOR consists of abstracts referenced as evidence for reactions curated in the mTOR signalling pathway [25], annotated for entities and events relevant to the pathway model formalism [7]. Multi-Level Event Extraction (MLEE) consists of abstracts in the blood vessel development subdomain that have been annotated using a comprehensive set of entity and event types encompassing levels of biological organisation from molecule to organism [26]. …”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that Method Precision Recall F1-Score SVM (Pyysalo et al, 2012) 81.44 69.48 75.67 SVM+W e (Zhou et al, 2014) 80.60 74.23 77.82 CNN (Wang et al, 2016a) 80 …”
Section: Category Wise Performance Analysismentioning
confidence: 99%
“…This task helped shift the focus of relation extraction efforts from identifying simple binary interactions to identifying complex nested events that better represent the biological interactions stated frequently in text. Existing approaches to this task include SVM (Björne and Salakoski, 2013) other ML based approaches (Riedel and McCallum, 2011;Miwa et al, 2010Miwa et al, , 2012 In our work, we take inspiration from the Turk Event Extraction System (TEES) (Björne and Salakoski, 2013) (the event extraction system for EVEX) that has consistently been the top performer in these series of tasks. They represent events using a graph format and break the event extraction task into separate multi-class classification tasks using SVM as their classifier.…”
Section: Related Workmentioning
confidence: 99%